Unconscious Emotion and Free-Energy: A Philosophical and Neuroscientific Exploration - Michael, Michael T. (Frontiers in Psychology, 2020)
Unconscious emotions are of central importance to psychoanalysis. They do, however, raise numerous conceptual problems. The most pertinent concerns the intuition, shared by Freud, that consciousness is essential to emotion, which makes the idea of unconscious emotion seem paradoxical. In this paper, I address this paradox from the perspective of the philosopher R. C. Roberts’ account of emotions as concern-based construals. I provide an interpretation of this account in the context of affective neuroscience and explore the form of Freudian repression that emotions may be subject to under such an interpretation. This exploration draws on evidence from research on alexithymia and utilizes ideas from free-energy neuroscience. The free-energy framework, moreover, facilitates an account of repression that avoids the homunculus objection and coheres with recent work on hysteria.